CrowdFund: CrowdFunding Decentralized Implementation on Ethereum Blockchain - Singh Bamber, Sukhvinder (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The Ethereum blockchain platform’s decentralised application (DAPP) called crowdfunding enables users to donate money for causes they care deeply concerned about. We can ensure that contributors engage in low-risk backing of emerging ventures and venture capitalists by leveraging blockchain and verifying their transactions and securing the sensitive data. More global supporters can be attracted by creators, which makes it simpler for them to raise significant sums of money quickly. There are a number of projects in the blockchain realm right now. Individuals or small dispersed teams who want to raise funding by issuing tokens have built on this platform to attract the potential contributors. The concept of raising funds through a crowdfunding site is simplified. With the help of global assistance of the public who may be interested to contribute in the campaign for a monetary incentive so that it is beneficial to the contributor as well as the creator and the cause for which the crowdfunding DAPP is being made.